2013
DOI: 10.3109/02699052.2013.765597
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral large traumatic basal ganglia haemorrhage in a conscious adult: A rare case report

Abstract: A case of a 38 year old fully conscious male, who presented with bilateral basal ganglia haematoma and extradural haematoma, is presented and the relevant literature is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
(14 reference statements)
0
25
0
Order By: Relevance
“…This may be a medicolegal issue; as to whether the patient had a spontaneous basal ganglia bleed leading to the subsequent head injury or it was the head injury, which caused the basal ganglia hematoma. This rare entity has been previously reported in literature by Yanaka 10 have mentioned the only case of large bilateral TBGH with a fully conscious patient unlike the above-stated reports where the patients all had a poor GCS. The exact pathogenesis of basal ganglia hematoma is unclear; however, it is suggested that when a strong impact occurs over the vertex, forehead, or occipital region, the shearing force causes the brain to be displaced through the tentorial notch.…”
Section: Discussionmentioning
confidence: 62%
“…This may be a medicolegal issue; as to whether the patient had a spontaneous basal ganglia bleed leading to the subsequent head injury or it was the head injury, which caused the basal ganglia hematoma. This rare entity has been previously reported in literature by Yanaka 10 have mentioned the only case of large bilateral TBGH with a fully conscious patient unlike the above-stated reports where the patients all had a poor GCS. The exact pathogenesis of basal ganglia hematoma is unclear; however, it is suggested that when a strong impact occurs over the vertex, forehead, or occipital region, the shearing force causes the brain to be displaced through the tentorial notch.…”
Section: Discussionmentioning
confidence: 62%
“…Fujioka et al proposed that a traumatic injury to middle cerebral artery could also be responsible for hemorrhages within the putamen [15]. Finally, Jain et al hypothesized that for their patient some degree of asymptomatic derangement of the microvasculature might have predisposed to the hematoma formation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al considered 2 cm in the greatest diameter as the cutoff to define small or large lesions [2]. In addition small hemorrhagic lesions seem to be more associated to diffuse axonal injury (DAI) [11]. Actually the proposed pathophysiology mechanisms for TBGH have similarities to the mechanisms responsible for DAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) We hypothesize that the patient had some degree of asymptomatic derangement of the microvasculature of the CC, that made the microvasculature more vulnerable to stretching and/or shearing forces; this condition predisposed the patient to hematoma formation when subjected to trauma. 23) We assumed that the initial hemorrhage spot on the CC caused by the mild impact was minimal enough that it was either undetectable even with high-definition CT or that it had been already washed out when the first CT was performed; thus no obvious local neurological sign was apparent right after the injury, but it gave rise to symptoms several weeks later, presenting as a massive hematoma. 24,25) Additionally, post-traumatic headache may mask underlying chronic bleeding which also prolonged the course.…”
Section: Discussionmentioning
confidence: 99%